Program of the Antarctic Syowa Station MST/IS Radar (PANSY) ST Observations ... : Stratospheric and tropospheric observations ... - Sato, Kaoru; Tsutsumi, Masaki; Sato, Toru; Nishimura, Koji; Kohma, Masashi; Hashimoto, Taishi (National Institute of Polar Research, 2020)
High resolution 3D wind velocity data observed by PANSY radar (69.0S, 39.6E). The PANSY radar is the first and the only MST/IS radar in the Antarctic region. Continuous operation has been started from 2012 with a partial subsystem. The upgraded full-system observation has been achieved in 2015.The peak transmission power is 520 kW and the area of the antenna array is 16,000 m^2. This metadata represents the stratosphere and troposphere (ST) observations.Altitude coverage of the ST observation is from 1,500 to 25,000 m. Time and height resolutions are about 3 minutes and 150 m, respectively. The estimates are obtained based on Doppler shift observed with the multi-beam (5-beam) method. The data is provided with NET-CDF format. Although the data have been processed after a careful screening for unexpected noise and interferences, they may contain systematic errors nevertheless. It is therefore recommended that you contact us and be advised for the use of data. ...